U.S. power in international higher education - Lee, Jenny J. (Rutgers University Press, 2021)
U.S. Power in International Higher Education explores how internationalization in higher education is not just an educational endeavor, but also a geopolitical one. By centering and making explicit the role of power, the book demonstrates the United States's advantage in international education as well as the changing geopolitical realities that will shape the field in the future. The chapter authors are leading critical scholars of international higher education, with diverse scholarly ties and professional experiences within the country and abroad. Taken together, the chapters provide broad trends as well as in-depth accounts about how power is evident across a range of key international activities. This book is intended for higher education scholars and practitioners with the aim of raising greater awareness on the unequal power dynamics in internationalization activities and for the purposes of promoting more just practices in higher education globally